Building a Strong Foundation: Using Advisory to Support Students in an Uncertain Time - Brie Healy (Middle Grades Review, 2021)
The purpose of this essay is to provide a practitioner perspective based on an action research project that investigated the question “How can building a strong advisory community support students to feel connected and promote engagement in a remote or hybrid learning environment?”. The goal was to encourage students’ sense of belonging and social connectedness to promote engagement and social-emotional well-being in response to the detrimental effects of the coronavirus pandemic. My middle grades colleagues and I focused our efforts on building strong advisory communities as we navigate an uncertain learning environment, because as one of them stated simply, “when the relationships are there, school works a lot better.”
Keywords: advisory; adolescents; support; relationships; social connectedness; COVID-19; coronavirus; social-emotional